1997
DOI: 10.1210/en.138.12.5541
|View full text |Cite
|
Sign up to set email alerts
|

Three New Members of the Mouse Prolactin/Growth Hormone Family Are Homologous to Proteins Expressed in the Rat

Abstract: A search of a mouse expressed sequence tag database for novel messenger RNAs (mRNAs) in the PRL/GH family has identified three clones that are homologous to the rat PRL-like protein A (PLP-A), PRL-like protein B (PLP-B), and decidual/trophoblast PRL-related protein (d/tPRP). Full-length complementary DNA clones for each of these three mouse mRNAs have been sequenced. Mouse PLP-A is predicted to be synthesized as a precursor of 227 residues and secreted as a glycoprotein of 196 amino acids; the secreted protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…PRL family genes have also been mapped to similar regions within the genome. In the mouse, PRL family genes are located on chromosome 13 (Jackson-Grusby et al 1988, Lin et al 1997a,b, Orwig et al 1997b, Dai et al 1998, Toft & Linzer 1999. Consistent with this pattern, genes for PLP-J, PLP-K and PLP-M were also mapped to the Prl locus on mouse chromosome 13.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…PRL family genes have also been mapped to similar regions within the genome. In the mouse, PRL family genes are located on chromosome 13 (Jackson-Grusby et al 1988, Lin et al 1997a,b, Orwig et al 1997b, Dai et al 1998, Toft & Linzer 1999. Consistent with this pattern, genes for PLP-J, PLP-K and PLP-M were also mapped to the Prl locus on mouse chromosome 13.…”
Section: Discussionmentioning
confidence: 81%
“…Expressed sequence tags (ESTs) isolated from mouse and rat uterine and extraembryonic cDNA libraries with homology to members of the PRL family have been found in the National Center for Biotechnology Information (NCBI) database (Bethesda, MD, USA). Perusal of this repository resulted in the demonstration of previously unidentified orthologs for mouse and rat PRL family members (Lin et al 1997a, Orwig et al 1997b, Müller et al 1998a, Sahgal et al 2000 and the discovery of novel members of the mouse and rat PRL gene families (Lin et al 1997b, Müller et al 1998b, Ishibashi & Imai 1999.…”
Section: Introductionmentioning
confidence: 99%
“…1997a, Müller et al 1998c, present study). The degree of similarity between the rat and mouse cDNAs is comparable to that observed for other PRL family members possessing rat and mouse homologs (PRL, Maurer et al (1981), Cooke & Baxter (1982), Linzer & Talamantes (1985); PL-I, Colosi et al (1987), Robertson et al (1990), Hirosawa et al (1994), Dai et al (1996a); PL-II, Duckworth et al (1986a), Jackson et al (1986), Dai et al (1996a); PLP-A, Duckworth et al (1986b), Lin et al (1997b), Müller et al (1998b); PLP-B, Duckworth et al (1988), Lin et al (1997b), Mü ller et al (1988b; decidual prolactin-related protein, Roby et al (1993), Lin et al (1997b), Orwig et al (1997b)). Based on the significant structural homologies, the two newly identified cDNAs were classified as rat homologs of PLF-RP and PLP-F.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage data from the C57BL/6J × Mus spretus backcross indicated that the Prlpa gene was located on Chr 13. Other members of the mouse PRL gene family have also been localized to Chr 13 (Jackson-Grusby et al 1988;Ko et al 1994;Lin et al 1997;Orwig et al 1997); however, their arrangement on Chr 13 has not been reported. Physical relationships of the PRL family genes along Chr 13 may provide insights into the nature of their coordinated tissue-and cell-specific expression patterns.…”
Section: Incorporating Mouse Genomementioning
confidence: 99%
“…Prolactin-like protein-A (PLP-A) is a member of the prolactin (PRL) gene family and is expressed by trophoblast cells of the developing rat and mouse chorioallantoic placenta (Lin et al 1997;Müller et al 1998). PLP-A has been proposed to participate in the control of maternal immunologic responses prerequisite for the establishment of pregnancy through its specific interactions with uterine natural killer cells (H. Müller and M.J. Soares, unpublished).…”
mentioning
confidence: 99%